2020
DOI: 10.1371/journal.pone.0229774
|View full text |Cite
|
Sign up to set email alerts
|

A model of crop diversification under labor shocks

Abstract: As demands on agriculture increase, food producers will need to employ management strategies that not only increase yields but reduce environmental impacts. Modeling is a powerful tool for informing decision-making about current and future practices. We present a model to evaluate the effects of crop diversification on the robustness of simulated farms under labor shocks. We use an example inspired by the Florida production system of high-value, labor-intensive fruits. We find that crop diversification to high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As foreign competition and domestic challenges such as labor shortages (Bampasidou and Salassi, 2019;Beal Cohen et al, 2020;Guan et al, 2015;Roka and Guan, 2018) and the phase-out of methyl bromide (Cao et al, 2019;Wu et al, 2020) increasingly erode the profitability of US growers, solutions must be found to make the industry viable and competitive. This applies not only to the fresh tomato industry but also to other major fresh produce commodities such as peppers (Biswas et al, 2018) and berries (Suh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As foreign competition and domestic challenges such as labor shortages (Bampasidou and Salassi, 2019;Beal Cohen et al, 2020;Guan et al, 2015;Roka and Guan, 2018) and the phase-out of methyl bromide (Cao et al, 2019;Wu et al, 2020) increasingly erode the profitability of US growers, solutions must be found to make the industry viable and competitive. This applies not only to the fresh tomato industry but also to other major fresh produce commodities such as peppers (Biswas et al, 2018) and berries (Suh et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Simulated Annealing (SA) and Particle Swarm Optimization (PSO) are employed in [24] to address a multi-crop allocation optimization problem. In [25], a crop allocation model is presented to deal with the problem of labor shortage which in turn impacts crop production. A Linear Programming (LP) based optimization model is presented in [26] to address the problem of land allocation for 10 crops.…”
Section: A Crop Planning Modelsmentioning
confidence: 99%
“…The literature discussed in [36]- [43] provides a guideline for sustainable agriculture and through this research, we explore the quality impact of advanced crop allocation on the overall environment. A benchmark table is presented in Table . 1 in which we present contributions of main studies that we followed [21], [25], [33], [34], the limitation of each study and eventually summarize our research. The compared research provides gaps in the development of the crop allocation model, and in research specific to the study area which helps in the identification of the problem statement.…”
Section: Sustainable Agriculturementioning
confidence: 99%
“…However, the U.S. fruit and vegetable industry has been facing major challenges in production and import competition. In recent years, growers of fruit and vegetables, which are labor-intensive crops, have reported challenges in hiring sufficient farm labor, especially in the peak harvesting months [4][5][6][7]. Moreover, rising labor costs have been trimming down growers' profit margins over the years [8].…”
Section: Introductionmentioning
confidence: 99%